Design and development of turning type magnetorheological finishing process - Garg, Prince (My University, 2015)
A new precision finishing process for finishing of cylindrical external surfaces using turning type magnetorheological finishing tool has been developed. To fulfill the needs for finishing external cylindrical surfaces such as groove, taper, step surfaces and threads, a turning type magnetorheological finishing process has been developed. A newly developed turning type magnetorheological finishing process is used for finishing external cylindrical surfaces, as tool tip is able to reach deeper grooves. For this reason the turning type magnetorheological finishing process has been developed for further applications with the aim of achieving finishing in the external cylindrical workpiece surfaces. At first simulation for turning type magnetorheological finishing tool were performed in MAXWELL ANSOFT V13 student version to study the magnetic flux density distribution at the tip of finishing tool. The second stage CAD model was designed for the turning type magnetorheological finishing tool to examine the shape and dimensions. With the designed parameters, a turning type magnetorheological finishing tool has been fabricated and attached at the selected Lathe machine. To know the process capability of the developed finishing setup, the design of experiments was carried out with major selected process parameters such as working gap, magnetizing current and workpiece rotating speed. The experiments plan and analysis have been done by using software DESIGN EXPERT- 9. The experimental responses were measured in terms of percentage change in Ra values. The experiments have been performed on each specimen at 90 minute of finishing time. On the basic of experimental results, the optimum process parameters were predicted from the regression model for maximum percentage change in Ra value. The scanning electron microscopy has been also used to know the final finished surface quality. The newly developed turning type magnetorheological finishing process finds its broad function in automotive, machine tool manufacturing, valve and pipe manufacturing industries etc.
ME-CAD/CAM-Thesis
Keywords: Magnetorheological; Finishing; Magnetorheological flux; denity; mechanical engineering; CAD/CAM; MED